A monocistronic transcript for a trypanosome variant surface glycoprotein. - Alarcon, C M (1994)
Many protein-encoding genes of African trypanosomes are transcribed as large polycistronic pre-mRNAs that are processed into individual mRNAs containing a 5' spliced leader and 3' poly(A). The 45- to 60-kb pre-mRNAs encoding some variant surface glycoproteins (VSGs) contain as many as eight unrelated coding regions. Here we identify the promoter for a metacyclic VSG gene that is expressed without duplication in a bloodstream trypanosome clone. This 70-bp promoter is located 2 kb upstream of the telomere-linked VSG gene and directs the synthesis of a monocistronic VSG pre-mRNA lacking the 5' spliced leader. Its sequence only slightly resembles those of other known trypanosome promoters, but it does cross-hybridize with several related sequences elsewhere in the genome. These results suggest that a new class of trypanosome promoters has been found, whose function is to initiate monocistronic transcription of those VSG genes normally expressed during the metacyclic stage.